Effects of Chitosan Nano Mouth Spray on Epithelial Thickness in the Socket Wound Healing (In vivo study) - Anggun Feranisa; Recita Indraswary; Silvi Anggraini (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: After tooth extraction, wounds are caused by removing teeth from the alveolar bone. The prevalence of the Indonesian population experiencing toothache is 23%. Tooth extraction occupied the top position, namely 54,3%. Wound healing after tooth extraction can cause risks and complaints from sufferers. The process of fast wound healing after a tooth extraction is the main thing that needs to be considered. Chitosan is a biomaterial that has been used to accelerate the healing process of extraction wounds. Purpose: This study aims to determine the effect of using chitosan nano mouth spray on epithelial thickness in the healing process of socket wounds after tooth extraction (in vivo study on male Wistar rats).Method: This research is a true experimental type with a post-test-only control group design. Thirty male Wistar rats were divided into three groups. K1, the treatment group was given nano mouth spray. K2, the positive control group, was given aloclair plus spray. K3, the negative control group, was given aquadest. They were then analyzed using one-way ANOVA and LSD tests.Result: The results showed no re-epithelialization was formed in each group or the thickness was 0. Because the epithelial layer has not yet formed, changes in fibroblas cells can be observed. The results showed a significant difference in the number of fibroblass between each treatment group.Conclusion: The conclusion obtained is that chitosan nano mouth spray has no effect on epithelial thickness in the socket wound healing process after tooth extraction in male Wistar rats on the 7th day after treatment. Chitosan nano mouth spray affected the number of fibroblast in the socket wound healing process after tooth extraction in male Wistar rats on the 7th day after treatment.